The Doctrine of German Neo-Liberalism in Terms of its Genesis and Practical Implementation - Čiegis, Remigijus; Vveinhardt, Jolita (Ekonomika, 2007)
The phenomenon of German neo-liberalism as a peculiar political-economic doctrine which became popular after World War It is analysed in the context of the ideology of neo-liberalism. Attempts have been made to show historical and cultural conditions which favoured the implementation of the ideas developed by W. Eucken, theoretician of the German neo-liberalism, and the representatives of the Freiburg school. The aim of the paper is to identify the peculiarities that make this economic thought different from classical neo-liberalism and have stimulated the development of the economy in post-war West Germany.